How to strengthen EHR usage in paediatric care: Designing a competency-based MOOC - Despina Papakonstantinou (SPOUDAI - Journal of Economics and Business, 2021)
Electronic health records (EHRs) are an essential aid to effective healthcare delivery, with significant benefits from their use. Nevertheless, the percentage of adoption of EHRs remains low and in the paediatric domain, it is even lower, partially cause to the fact that sufficient training is not provided to paediatric healthcare professionals. Usage can be increased through enhanced training that provides accurate information when and where it is needed and enables users' substantial participation to instil their knowledge and expertise in EHR usage. Moreover, EHR training can be accelerated if the content of training materials is based on competency models that meet the needs of paediatricians, paediatric nurses and practitioners. Recently, considerable effort has been made to develop Massive Open Online Courses (MOOCs) as a means of online training with no restrictions by location and time. Better training is expected to increase the use of EHR data, leading to optimal medical, and containing medical costs. On these grounds, this paper outlines the design of a MOOC service based on the competencies that paediatric healthcare professionals need to acquire to optimally operate through the EHR system at any time, either at the point of care or no.
Keywords: D83; I12; I18; I20; 330; EHRs; Paediatrics; MOOC; Learning; Competencies